The different types of burns and their respective treatments (Research, Society and Development, 2023)
Detail the different types of burns and analyze the methods used to treat burns in their different degrees. This article is an integrative literature review. The databases of scientific articles were used to perform the searches: Us National Library Of Medicine (PUBMED) and Scientific Electronic Library Online (SCIELO). The terms were used to meet the theme: “Burn” AND “Thermal injury” AND “treatment”. The temporal cut includes articles published between 1991 and 2022, with priority on more current articles that addressed the proposed themes. Burns differ in terms of type and also according to the degree of injury. According to the type of burns we have heat burns, which are the most common, we also have chemical burns and electrical burns. As for the degree of injury, we have first-degree burns (for example, sunburn) which are characterized by erythema, pain, without blistering. We also have second-degree burns, which are characterized by a red or mottled appearance and the presence of edema, and unlike first-degree burns, they have blisters. Third-degree burns on the surface are painless, due to the damage caused to the nerves that carry pain information to the skin, and are generally dry and may be red and not change color upon local compression. The treatment for these burns is varied and changes according to the degree of the injury, ranging from simple hydration to even skin grafts.